Confidentiality and security of information in the public health-care facilities to curb HIV/AIDS trauma among patients in Africa. Issue 8 (2nd December 2020) - Marutha, Ngoako Solomon; Mosweu, Olefhile
Abstract : Purpose: This study sought to investigate a framework for ensuring the confidentiality and security of information at the public health-care facilities to curb HIV/AIDS trauma among patients in Africa. In most instances, trauma to HIV/AIDS patients accelerate because of their personal information relating to the state of illness leaks to public people. Design/methodology/approach: This qualitative study used literature to study confidentiality and security of information at the public health-care facilities to curb HIV/AIDS trauma among patients in Africa. Findings: The study revealed that confidentiality and security of information has been neglected, in most instances, at the health-care facilities, and this has, to some extent, affected HIV/AIDS patients negatively, leading to trauma, stigma and skipping of treatment by patients resulting in accelerated mortality among chronic patients. The study recommends that patients' information be always strictly controlled and kept confidential and secured at all the times, especially that of HIV/AIDS patients. Practical implications: The proposed framework can be used by health-care facilities to guide the management and promotion of the confidentiality and security of information in the public health-care facilities to curb additional trauma to HIV/AIDS patients in the context of Africa, and even beyond. Originality/value: The study provides a framework to ensure the confidentiality and security of information at the public health-care facilities to curb additional trauma to HIV/AIDS patients.